Reliability of blood inflammatory markers at constant real-life workloads over time: Study protocol - Tessy Luger; Felix Uhlemann; Florestan Wagenblast; Thomas Läubli; Barbara Munz; Manfred Schmolz; Monika A. Rieger; Benjamin Steinhilber (PLoS ONE, 2025)
Background Work-related musculoskeletal disorders (WMSDs) are prevalent in occupations characterised by high repetition and high force demands. Both factors not only evoke inflammatory and degenerative processes in affected musculoskeletal tissue, but also systemic responses identified by biomarkers in blood serum. Clarifying methodological aspects of biomarkers may provide insights into their predictive role in the pathway of developing WMSDs. This study will primarily assess reliability of systemic inflammatory biomarkers (CRP, TNF-α, IL-6, IL-1β) and immune cell reactivity by repeated measures in workers with constant workloads over time. Methods This observational cross-sectional study will include two groups of workers: exposed group including workers exposed to higher upper-extremity physical workloads, especially affecting the elbow/forearm/hand-area; unexposed group, including office workers exposed to lower upper-extremity physical workloads. Recruited persons are screened against eligibility criteria followed by a medical anamnesis and blood analysis. Enrolled participants undergo nine repeated measurements once every two weeks, taking blood among others. Blood analyses will determine values of systemic inflammatory biomarkers and reactivity of immune cells. The absolute test-retest reliability of biomarkers and immune cell reactivity over time is assessed by the intra-class correlation coefficient applying two-way mixed-effects models. The relative test-retest reliability is assessed by the standard error of measurement. Discussion Knowledge of and models currently describing the pathological role of systemic inflammatory biomarkers are based on highly-controlled laboratory rat experiments. This study has the strength of assessing a human population under real-life conditions. The major challenge is in participant recruitment given the intensive and complex study design. The results of this study could provide fundamentals for initiating a cohort study and be used for developing work-related stress-recovery concepts for occupations with different physical demands to identify workers who may be at risk for developing WMSDs. German Clinical Trials Register (DRKS00031872, 25 May 2023).